Interactive effect of leader ethicality and competency on Chinese customs officers’ organizational citizenship behaviors - Fang, Zhenbang; Hua, Min; Bao, Yuanjie; Sun, Qi (Frontiers in Psychology, 2023)
The dual qualities of an effective leader—ethicality and competency—have long been identified but seldom empirically examined. Using survey data from 329 Chinese customs officers collected in December 2022, this study investigates whether ethical leadership influences customs officers’ organizational citizenship behaviors indirectly through work engagement and trust in leader. Following the interactive approach, we further postulate that leader competency can accentuate these indirect relationships. Mplus 8.3, SPSS 26.0 and Hayes’ PROCESS macro for SPSS were used to conduct statistical analyses including descriptive statistical analysis, correlation analysis, common method deviation analysis, confirmatory factor analysis, and regression analysis. The results reveal that work engagement and trust in leader act as mediators in the ethical leadership and organizational citizenship behaviors relationship. Moreover, these indirect relationships are stronger when customs officers perceive their leaders are more competent. Theoretical and practical implications are discussed.